Pulsed field ablation vs sham ablation to treat atrial fibrillation (the PFA-SHAM trial) - Osmancik, Pavel; Neuzil, Petr; Karel, Tomas; Waldauf, Petr; Hozmanova, Jana; Hozman, Marek; Kralovec, Stepan; Herman, Dalibor; Petru, Jan; Sediva, Lucie; Fischer, Jakub; Stepanek, Lubomir; et al. (Heart rhythm O2, 2025)
BACKGROUND: Compared with antiarrhythmic drugs, pulmonary vein isolation (PVI) reduces atrial fibrillation (AF) recurrences and AF burden. All but one previous study was unblinded, raising the possibility of a placebo effect of catheter ablation. OBJECTIVE: This study aimed to compare PVI using pulsed field (PF) energy to a sham procedure in patients with symptomatic AF. METHODS: PFA-SHAM is a single-blind, randomized trial of symptomatic patients with paroxysmal or persistent AF, and an Atrial Fibrillation Effect On Quality-of-Life (AFEQT) questionnaire score ≤50. At enrollment, all patients receive an implantable cardiac monitor, and an electrophysiology study is scheduled 30 days later. After excluding supraventricular tachycardia as a cause of AF, patients are randomized to either sham or PVI using the pentaspline PF ablation catheter. The 2 co-primary outcomes are (1) freedom from recurrent AF, atrial tachycardia, or atrial flutter lasting >30 seconds, assessed as time to first recurrence (post 2-month blanking); and (2) change in quality of life according to the AFEQT score at 6-month post-ablation, compared between groups. Cross-over is permitted for patients with significant symptom worsening according to pre-specified rules. Key secondary outcomes include AF burden at 6 months, and differences in the Hospital Anxiety and Depression Scale, compared between groups. RESULTS: Enrollment in the study was initiated in September 2023. As of January 2025, 50 patients have been enrolled. Results are expected by the end of 2025. CONCLUSION: This study compares PVI using PF energy to a sham procedure. The study will assess the effect of PVI on AF recurrences and quality of life. TRIAL REGISTRATION NUMBER: NCT02426944.
Keywords: Atrial fibrillation; Pulsed field ablation; Implantable cardiac monitor; Randomized; Sham; Clinical trial